The Internal Conduit System of the Swine Inverted Lymph Node - Dubreil, Laurence; Ledevin, Mireille; Hervet, Caroline; Menard, Déborah; Philippe, Claire; Michel, François J.; Larcher, Thibaut; Meurens, François; Bertho, Nicolas (Frontiers in Immunology, 2022)
Lymph nodes (LN) are the crossroad where naïve lymphocytes, peripheral antigens and antigen presenting cells must contact together in order to mount an adaptive immune response. For this purpose, LN are highly organized convergent hubs of efferent blood and lymphatic vessels that, in the case of B lymphocytes, lead to the B cell follicles. Herein take place the selection and maturation of B cell clones producing high affinity antibodies directed against various antigens. Whereas the knowledge on the murine and human LN distribution systems have reached an exquisite precision those last years, the organization of the antigens and cells circulation into the inverted porcine LN remains poorly described. Using up to date microscopy tools we described the complex interconnections between afferent lymphatics and blood vessels, perifollicular macrophages, follicular B cells and efferent blood vessels. We observed that afferent lymphatic sinuses presented an asymmetric Lyve-1 expression similar to the one observed in murine LN, whereas specialized perifollicular sinuses connect the main afferent lymphatic sinus to the B cell follicles. Finally, whereas it was long though that mature B cells egress from the inverted LN in the T cell zone through HEV, our observations are in agreement with mature B cells accessing the efferent blood circulation in the efferent, subcapsular area. This understanding of the inverted porcine LN circuitry will allow a more accurate exploration of swine pathogens interactions with the immune cells inside the LN structures. Moreover, the mix between similarities and differences of porcine inverted LN circuitry with mouse and human ‘normal’ LN shall enable to better apprehend the functions and malfunctions of normal LN from a new perspective.